2001
DOI: 10.1046/j.1523-1755.2001.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Tubular NF-κB and AP-1 activation in human proteinuric renal disease

Abstract: On the whole, our results show that a tubular overactivation of NF-kappaB and AP-1 and a simultaneous up-regulation of certain proinflammatory and profibrogenic genes are markers of progressive renal disease in humans. Increased activation of solely NF-kappaB and/or AP-1 may merely indicate the response of tubular renal cells to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
131
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 30 publications
10
131
2
3
Order By: Relevance
“…Vertical hatched marks on the survival curves indicate the end of follow-up for patients who did not develop ESRD. and nucleus) [10,11]. The use of SWH in the present study showed a distribution of NF-kB staining similar to that described above.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Vertical hatched marks on the survival curves indicate the end of follow-up for patients who did not develop ESRD. and nucleus) [10,11]. The use of SWH in the present study showed a distribution of NF-kB staining similar to that described above.…”
Section: Discussionsupporting
confidence: 88%
“…Once activated, NF-kB, activates the transcription of target genes involved in inflammation, immunity, apoptosis, cell proliferation and differentiation [8,16]. Using southwestern histochemistry (SWH), some previous studies demonstrated that NF-kB played a pivotal role in proteinuric nephropathy, such as minimal change disease, idiopathic membranous nephropathy, diabetic nephropathy and lupus nephritis [10,11,22]. Indeed, proteins have been shown to activate tubular expression of chemokines, mainly MCP-1, in proximal tubules through an NF-kB-dependent mechanism [6].…”
Section: Introductionmentioning
confidence: 99%
“…In general, NF-B activates in macrophages and glomerular (including podocytes in proteinuric diseases) and tubular parenchymal cells and correlates with parameters of severity of disease such as proteinuria or inflammation. 59,[61][62][63][64][65] These data have been interpreted as supportive for the role of NF-B in promoting inflammation; however, inflammation itself will promote NF-B activation, and because these data are descriptive, the precise role of the various NF-B complexes in human kidney injury remains uncertain. Functional evidence of NF-B activation has been obtained by transcriptomics-based pathway mapping 66 ; in progressive diabetic nephropathy, there is upregulation of 54 of 138 known NF-B targets with special enrichment in NF-B/IRFF module target genes.…”
Section: Nf-b Activation In Experimental and Human Renal Diseasementioning
confidence: 99%
“…Aberrant regulation of NF-B may result in inflammatory and autoimmune diseases, impair antiviral immune responses, and contribute to malignant cellular transformation. 1-3 Activation of NF-B, with subsequent production of cytokines, chemokines, and adhesion molecules, is an important component of the pathogenesis of several forms of renal disease, including diabetic nephropathy (DN), 4,5 hypertensive nephrosclerosis (HN), 6,7 IgA nephropathy (IgAN), 8 membranous glomerulopathy, 9 and HIV-associated nephropathy. 10 -12 The canonical NF-B activation pathway can be induced by a variety of stimuli, including TNF-␣.…”
mentioning
confidence: 99%